(3GdfXGe GdeMGSHj aj GdhMOGJ GdMchejI h eLGdGJ JWhjQg (B/s - (3RfcfI, CSGeI QTjO SdeGfs ((3YeGf(B: s (3OGQ OLdI(B, s, 2008)
(3jMJhj gPG GdcJGH Ydi(B:(3GdEWGQ GdfXQj ddeMGSHI GdMchejI,Jbjje GdfXGe GdeMGSHj GdMchej GddGeQcRj aj LGeYI UdGM GdOjf (B- (3CQHjd,eLGdGJ JWhjQ GdfXGe GdeMGSHj GdMchej GddGeQcRj aj LGeYI UdGM GdOjf (B- (3CQHjd(B. s
(3HjHdjhZQGajG U(B. 205(3; edGMb U(B.219s
Keywords: (3GOGQI YGeIs; (3McheI eMdjIs; (3eMGSHI eGdjIs